Origin of the moon. New concept : geochemistry and dynamics - Galimov, Ė. M. (Ėrik Mikhaĭlovich); Krivtsov, Anton M. (De Gruyter, 2012)
The origin of the Moon remains an unsolved problem of the planetary science. Researchers engaged in celestial dynamics, geophysics, and geochemistry are still discussing various models of creation of our closest cosmic neighbour. The most popular scenario, the impact hypothesis involving a collision early in the Earth's history, has been substantially challenged by the new data. The birth and development of a planet-moon system always play a role in the formation of an entire planetary system around our Sun or around another star. This way, the story of our Moon acquires broader ramifications.